Efficacy of Two Caries Detector Dyes in the Diagnosis of Dental Caries - M. Javaheri; S. Maleki-Kambakhsh; Sh. Etemad-Moghadam (Tehran University of Medical Sciences, 2010)
Objective: The aim of the present study was to evaluate the efficacy of two caries detector dyes in the diagnosis of dental caries. Materials and Methods: Twenty extracted human posterior teeth without pulpal exposure were sectioned mesiodistally through the center of the lesions using a water-cooled disk. The tooth halves were randomly divided into two groups and treated with Caries Detector (CD) and Caries Check (CC) detector dyes. Access cavities were prepared followed by caries removal and dye application. All cavities were arbitrarily divided into two right and left sections and excavation of the stained areas was performed on the left parts, while the right sections remained untouched. Bacterial penetration into dentinal tubules was evaluated using Gram-stained decalcified sections under light microscopy. Sensitivity and specificity of both dyes were calculated. Results: The sensitivity of CD and CC were 74% and 71%, respectively. The specificity obtained for both dyes was 100%. Conclusion: Considering the low sensitivity of the dyes evaluated in the present study, it seems that they may not be reliable when used as the sole diagnostic technique for detection of carious lesions in posterior teeth.